Use of healthcare services and therapeutic measures associated with new episodes of acute low back pain- related disability among elderly people: a cross-sectional study on the Back Complaints in the Elders - Brazil cohort - Amorim, Juleimar Soares Coelho de; Rocha, Vitor Tigre Martins; Lustosa, Lygia Paccini; Pereira, Leani Souza Máximo (São Paulo Medical Journal, 2021)
BACKGROUND: Patients with low back pain frequently undergo a variety of diagnostic and therapeutic interventions, but some of these have uncertain effectiveness. This highlights the importance of the association of healthcare services and therapeutic measures relating to disability. OBJECTIVE: To analyze the use of healthcare services and therapeutic measures among Brazilian older adults with disability-related low back pain. DESIGN AND SETTING: Observational cross-sectional study on baseline assessment data from the Back Complaints in the Elders - Brazil (BACE-B) cohort. METHODS: The main analyses were based on a consecutive sample of 602 older adult participants in BACE-B (60 years of age and over). The main outcome measurement for disability-related low back pain was defined as a score of 14 points or more in the Roland Morris Questionnaire. RESULTS: Visits to doctors in the previous six weeks (odds ratio, OR = 1.82; 95% confidence interval, CI 1.22-2.71) and use of analgesics in the previous three months (OR = 1.57; 95% CI 1.07-2.31) showed statistically significant associations with disability-related low back pain. The probability of disability-related low back pain had an additive effect to the combination of use of healthcare services and therapeutic measures (OR = 2.57; 95% CI 1.52-4.36). The analyses showed that this association was significant among women, but not among men. CONCLUSIONS: Occurrence of the combined of consultations and medication use was correlated with higher chance of severe disability among these elderly people with nonspecific low back pain. This suggested that overuse and “crowding-in” effects were present in medical services for elderly people.